Emerging Technologies And The Islamic Creative Economy: How Can Ethics And Innovation Work Together? - Abrar, Muhammad; Sari, Cut Meuthia (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
The rapid development of the digital economy and emerging technologies such as Artificial intelligence (AI), blockchain, fintech, and the metaverse has created new opportunities for the growth of the Islamic creative economy. This study examines how these evolving technologies can synergize with Islamic ethical values to support the development of the Islamic creative economy through a bibliometric approach and a review of recent literature. The findings reveal that academic trends show significant growth in the study of the Islamic digital economy, with a particular focus on ethics, inclusion, and sustainability. The integration of maqāṣid al-sharīʿah (ḥifẓ al-dīn, ḥifẓ al-nafs, ḥifẓ al-‘aql, ḥifẓ al-nasl, and ḥifẓ al-māl) has proven to be an essential normative framework in ensuring that digital innovations such as AI, blockchain, fintech, and IoT remain aligned with Islamic values. Emerging technologies play a strategic role in enhancing consumer trust, transparency, and market legitimacy; however, their implementation continues to face challenges related to infrastructure readiness, digital literacy, and adoption costs, particularly for micro, small, and medium enterprises (MSMEs). This study proposes an ethical innovation framework based on maqāṣid al-sharīʿah that emphasizes the balance between commercial and ethical values. The findings highlight that the development of the Islamic creative economy is not solely driven by efficiency and profit but also by social and moral sustainability, thereby contributing to the strengthening of an inclusive and globally competitive Islamic digital ecosystem.